Implementasi Wakaf Uang pada Islamic Microfinance Institution di Era Society 5.0 - Latifah, Eny; Hidayah, Mia Lailatul (Fakultas Syariah INSURI Ponorogo, 2020)
The purpose of this reseach is to find out the implementation in channeling the endoWment of money to the authorities and the motives of customers in the endowment of money in The Islamic Microfinance Institutions called KSPPS Mandiri Sejahtera in Era Society 5.0. The resuts of the reseach are the process of channeling the results of Waqf money starting from Waqif handing over money to kspps Mandiri Sejahtera through the purchase of Waqf voucher money . then managed endowment fund and distributed funds to people in need. Motives of customers at KSPPS BMT Mandiri Sejahtera have a motive, Which is forced by the relevant regulations, such as compliance with payment administration, staff who work there every month are deducted from their waqf money. The next motive in managing money Waqf money voucher seems to force Waqif because most do not have the urge of oneself to endowment but compulsion and even the obligation to pay endowment for money to get what customers want, such as internship, field work practices, and reseach. Tujuan penelitian adalah ingin mengetahui impelementasi dalam menyalurkan wakaf uang kepada pihak yang berwenang, dan motif nasabah dalam wakaf uang yang ada di Islamic Microfinance Institution yang bernama KSPPS Mandiri Sejahtera di Era Society 5.0. Hasil penelitian adalah Proses penyaluran hasil wakaf uang dimulai dari waqif menyerahkan uang kepada KSPPS BMT Mandiri Sejahtera melalui pembelian voucher wakaf uang Kemudian di kelola dana wakaf uangnya dan salurkan kepada orang-orang yang membutuhkan. Motif nasabah di KSPPS BMT Mandiri Sejahtera memiliki motif, yaitu motif yang terpaksa dengan peraturan yang terikat seperti pemenuhan administrasi pembiayaan, staf yang bekerja disana setiap bulan gajinya akan dipotong untuk wakaf, motif selanjutnya dalam melakukan pengelolaan voucher wakaf ini terkesan memaksa waqif karena kebanyakan tanpa dorongan dari diri sendiri untuk wakaf melainkan paksaan bahkan kewajiban untuk membayar wakaf uang demi mendapatkan apa yang diinginkan nasabah, seperti magang, Praktek Kerja Lapnagan, dan Penelitian.